Menggali Nilai Moral Sosial dari Tradisi Budaya Soro Noto Masyarakat Jontona dalam Perspektif Filsafat Konfusianisme - Erfianus Moat Terang; Reinaldus Sina Ama (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2025)
This study aims to find out the social moral values ​​contained in the soro noto cultural tradition in the Jontona village community. The social moral values ​​contained in the cultural tradition will be juxtaposed with the theory of Confucian philosophy. The juxtaposition will be a compass for researchers to find the content of social moral values ​​contained in the soro noto cultural tradition. This study actually uses two methods, namely the interview method and literature review. So far, the researcher's investigation has found that the social moral values ​​contained in the soro noto cultural tradition based on the Confucian philosophy are the values ​​of solidarity, the value of kindness and the value of responsibility. In fact, the values ​​that have been mentioned can be used as life lessons for someone to become more mature in living in a community and strengthening the bonds of brotherhood and family in the social environment.